Will the Thai ABC Car Owners, Buy a Smart ABC Car? a Case Study in Bangkok Metropolis - Sittichainarong, Keerati; Loh, Aaron; Methavasaraphak, Preecha; Barnes, John (International Journal of Engineering and Technology, 2018)
Thailand is the biggest manufacturer of trucks and cars outside of Japan and China in Asia. Many had reported that "smart" technology especially that which leads towards driverless or autonomous vehicles will be the most important single development that will affect the automobile industry both domestically and globally.Â  Hence this research is therefore on the readiness of Thai car owners to adopt the new technology and the intention to purchase a smart car in the near future. Specifically, it is a case study on the influential factors affecting the intent to purchase a smart car by owners of a top Japanese brand in Bangkok. A questionnaire survey was conducted on 385 existing car owners of the Japanese brand under consideration in metropolitan areas of Bangkok and the data returned analyzed by multiple linear regression. The outcome of the research pointed towards â€˜Self-identityâ€ and â€˜Emotional connectionâ€™ as the most influential factors towards the intent to purchase a smart car.Â Â
Keywords: Thailand is the biggest manufacturer of trucks and cars outside of Japan and China in Asia. Many had reported that "smart" technology especially that which leads towards driverless or autonomous vehicles will be the most important single development that